On the Possibilities and Considerations of Interfacing Ultra‐High Vacuum Equipment with an Electrochemical Setup. Issue 22 (18th September 2019) - Maagaard, Thomas; Tiwari, Aarti; Chorkendorff, Ib; Horch, Sebastian
Abstract: Efficient electrocatalysts are required in order for electrocatalysis to play a large role in a future largely based on renewable energy sources. To rationally design these catalysts we need to understand the fundamental origin of their activities. In order to elucidate the relationship between catalyst structure and electrochemical behaviour, we investigate well‐defined single‐crystal catalysts in a UHV chamber interfaced with an electrochemical setup. Using the capabilities of UHV based methods, we can prepare more complex surface structures than it is possible with traditional EC methods and investigate their electrochemical behaviour. We exemplify this by showing results from both clean and intentionally structured Pt(111), Cu(111) and Pt/Cu(111). Abstract : Ultra‐high‐vacuum‐based techniques allow for the preparation of well‐defined samples, which in turn provides the foundation for a better understanding of the electrochemical behavior of a given material. As examples of this, the authors show how the influence of step and terrace sites on the blank voltammetries of Pt(111) and Cu(111) differ from one another. Tools like this can be used as a way to establish electrochemical benchmarks of various samples.